CURRENT MANAGEMENT OF POLYPOIDAL CHOROIDAL VASCULOPATHY - Ciputra, Fredy (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Currently, there are several treatment options that can be offered to patients with PCV, including photodynamic therapy, administration of anti-vascular endothelial growth factor (anti-VEGF) agents, thermal laser, or a combination of these. Currently, PDT has the highest potential as it is a therapeutic option targeted at the choroid. Although PDT has been recognized as the standard treatment for PCV due to its high regression rate and good functional outcomes, it also has some disadvantages. Initially, PDT treatment for PCV was found to have complications such as acute vision loss and massive subretinal haemorrhage. These complications have been reduced with the introduction of anti-VEGF agents in PCV management. There is no specific anti-VEGF agent that has shown superiority over others. Thermal laser is an effective and relatively cheaper modality of treatment compared to PDT. Thermal laser plays an important role in the management of PCV in extrafoveal, peripapillary, and peripheral areas. Combination therapy is an attractive option for patients with PCV which can provide better polyp closure and visual outcomes, and also a decrease in complication rates compared to monotherapy.